First admissions to psychiatric hospitals in south-east England in 1976 among immigrants from Ireland. Issue 6279 (6th June 1981) - Dean, G; Downing, H; Shelley, E
Abstract : Irish male immigrants had twice and female immigrants 1.7 times the expected number of first admissions to psychiatric hospitals in south-east England in 1976 when the expected number was based on the age- and sex-standardised rates of first admission of the population born in the United Kingdom living in the region. Admissions for alcoholism and alcoholic psychosis were five times higher in men and four times higher in women, and for schizophrenia 2.4 times as high in both sexes, as expected from these rates. When the expected number of first admissions was based on the age- and sex-standardised rates among Irish people living in Ireland the immigrants had fewer admissions than expected. Among migrants from Northern Ireland the number of first admissions was significantly greater than expected. Admissions for alcoholism and alcoholic psychosis in men and women combined were seven times the expected number based on the UK rates. There was no significant difference in the proportion of single people between the Irish immigrants and people born in the UK. Marital state, socioeconomic group, and occupation may partly account for the high number of admissions for alcoholism and schizophrenia among Irish people living in south-east England.